2015
DOI: 10.1093/mnras/stv1853
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a red supergiant counterpart to RX J004722.4–252051, a ULX in NGC 253

Abstract: We present two epochs of near-infrared spectroscopy of the candidate red supergiant counterpart to RX J004722.4-252051, a ULX in NGC 253. We measure radial velocities of the object and its approximate spectral type by cross-correlating our spectra with those of known red supergiants. Our VLT/X-shooter spectrum is best matched by that of early M-type supergiants, confirming the red supergiant nature of the candidate counterpart. The radial velocity of the spectrum, taken on 2014, August 23, is 417 ± 4 km s −1 .… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 53 publications
(62 reference statements)
3
24
0
Order By: Relevance
“…Based only on photometry, of the 38 detected NIR counterparts, 20 have NIR colours and/or magnitudes consistent with an RSG, 11 are preliminarily classified as stellar clusters, 6 are consistent with being an AGN, and 1 is too faint to be either an RSG or an SC/AGN (see Table B1). After a spectroscopic follow-up of 12 out of these 38 counterparts, we confirmed 5 RSGs (Heida et al 2015a(Heida et al , 2016, and this work), while 4 sources photometrically classified as RSG turned out to be nebulae (Heida et al 2016;López et al 2019, and this work). For the remaining three followed-up sources, one RSG candidate is a background AGN (this work), one stellar cluster candidate turned out to be a nebula (this work; see Table B1), and the last RSG candidate is too faint to be classified.…”
Section: Detected Nir Counterpartssupporting
confidence: 71%
See 1 more Smart Citation
“…Based only on photometry, of the 38 detected NIR counterparts, 20 have NIR colours and/or magnitudes consistent with an RSG, 11 are preliminarily classified as stellar clusters, 6 are consistent with being an AGN, and 1 is too faint to be either an RSG or an SC/AGN (see Table B1). After a spectroscopic follow-up of 12 out of these 38 counterparts, we confirmed 5 RSGs (Heida et al 2015a(Heida et al , 2016, and this work), while 4 sources photometrically classified as RSG turned out to be nebulae (Heida et al 2016;López et al 2019, and this work). For the remaining three followed-up sources, one RSG candidate is a background AGN (this work), one stellar cluster candidate turned out to be a nebula (this work; see Table B1), and the last RSG candidate is too faint to be classified.…”
Section: Detected Nir Counterpartssupporting
confidence: 71%
“…Of these 33 NIR sources, 19 had the absolute magnitude consistent with an RSG. So far, we performed spectroscopic follow-up observations for 7 out of these 19 candidate RSGs and confirmed the RSG nature for 3 counterparts: ULX RX J004722.4−252051 (in NGC 253; Heida et al 2015a), ULX J022721+333500 (in NGC 925), and ULX J120922+295559 (in NGC 4136; Heida et al 2016). Additionally, we discovered that four counterparts, initially classified as RSG based on photometry, are actually nebulae partially powered by the X-ray emission of the ULX: ULX J022727+333443 (in NGC 925), ULX J120922+295551 (in NGC 4136), ULX Ho II X-1 (in Holmberg II; Heida et al 2016), and [SST2011] J110545.…”
mentioning
confidence: 60%
“…The effects of the bright ULX on its environment has been seen in other Hii regions surrounding (or close to) a ULX (e.g. Mucciarelli et al 2005;Heida et al 2015). Since the presence of the ULX seems to affect the line flux ratios of J1105, and its radial velocity is consistent with the radial velocity of NGC 3521 at that position, we deem it likely that the ULX and the nebular source are physically related.…”
Section: The Ulx Counterpartmentioning
confidence: 72%
“…Currently, we have no independent observational constraints on the nature of the stellar companion in NGC 5907 ULX1 owing to both its distance and the obscuring column toward this source (Ñ 10 H 22 cm −2 ; the host galaxy NGC 5907 is seen edge-on). However, Heida et al (2014Heida et al ( , 2015 have recently reported a number of ULXs with candidate red supergiant companions, demonstrating that some of the ULX population likely do have evolved counterparts. Indeed, if we assume Roche-lobe overflow and that the period is orbital, we can estimate a density for the stellar counterpart of r~´-3 10 5 g cm −3 (Faulkner et al 1972), implying the counterpart may be either an M giant or an F supergiant (Drilling & Landolt 2000).…”
Section: Discussionmentioning
confidence: 99%